Incretin-based drugs and hospitalization for heart failure in the clinical practice: A nested case-control study. (December 2018) - Santucci, C.; Franchi, M.; Staszewsky, L.; La Vecchia, C.; Latini, R.; Merlino, L.; Corrao, G.; Bosetti, C.
Highlights: Incretin-based drugs have been suggested to increase the risk of hospitalization for heart failure in clinical trials. Incretin-based drugs are not associated with an increased risk of hospitalization for HF in real-world data from Italy. These data support the cardiovascular safety of incretin-based drugs in the clinical practice. Abstract: Background and aims: There are concerns that incretin-based antidiabetic drugs – including dipeptidyl peptidase 4 (DPP-4) inhibitors and glucagon-like peptide-1 (GLP-1) receptor agonists – increase the risk of hospitalization for heart failure (HF). To further analyse this issue, we conducted a nested case-control study within a cohort of antidiabetic users in a real world setting. Methods and results: Within a cohort of 133, 639 subjects with a first prescription of an antidiabetic drug (new-users) between 2010 and 2016 in Lombardy, Italy, and were followed-up to 2016, we identified 4057 subjects with a first hospitalization for HF and 80, 450 controls matched on sex, age, and date of cohort-entry. The multivariate odds ratios (ORs) of HF in relation to current use of incretin-based drugs as compared to current use of two or more oral antidiabetics was 1.06 (95% confidence interval, CI, 0.83–1.35), with no evidence of a trend in risk with increasing duration of use. The corresponding ORs were 1.10 (95% CI 0.85–1.41) for DPP-4 inhibitors and 0.84 (95% CI 0.48–1.47) for GLP-1 receptor agonists. Estimates were consistent in various sensitivity analyses. Conclusions: This study indicates that incretin-based drugs are not associated with an increased risk of hospitalization for HF, thus providing further reassurance on the cardiovascular safety of these antidiabetic drugs in the clinical practice.